Akuntabilitas Instansi Pemerintah dalam Bidang Pendidikan di Era Otonomi Daerah - Muhamad Hasanudin Buhory (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2007)
The purpose of this study is to examine the accountability of an education institution in implementing compulsory education program in this decentralization era. This institution, that is, Education Institution of Bangkalan Regency, was found to have undertaken accountability by endorsing reports on the process and results using standards and criteria established by the government. Schools, however, haven't reported their accountability to this institution.